Unfulfilled promises of the consultation approach: the limits to effective indigenous participation in Bolivia’s and Peru’s extractive industries - Flemmer, Riccarda; Schilling-Vacaflor, Almut (Third World Quarterly, 2016)
Indigenous peoples’ right to prior consultation and to informed consent represents the basis of the new global model shaping state–indigenous relations. Consultation processes promise to enable indigenous people to determine their own development and are especially promoted when extraction projects with significant socio-environmental impacts are planned on indigenous lands. In this article we draw on debates on participatory development in order to analyse the first state-led consultations in Bolivia’s and Peru’s hydrocarbon sectors (2007–14). The analysis shows that effective participation has been limited by (1) an absence of indigenous ownership of the processes; (2) indigenous groups’ difficulties defending or even articulating their own visions and demands; and (3) limited or very general outcomes. The study identifies real-life challenges, such as power asymmetries, a ‘communication hurdle’ and appropriate timing – as well as simplistic assumptions underlying the consultation approach – that account for the unfulfilled promises of this new model.
CRIS-Team Scopus Importer:2023-11-20
Keywords: Bolivia; extractive industry; free; prior and informed consent (FPIC); indigenous people; participatory development; Peru; Prior consultation